Поселение на юго-западном склоне горы Сокол - Джанов, А.В. (Археологический альманах, 2012)
В 1999 г. велись исследования поселения на юго-западном склоне г. Сокол. Впервые памятник был открыт в 1967 г. М.А. Фронджуло и тогда же была произведена разведочная шурфовка. На поселении был заложен шурф размерами 2 х 2 м в котором обнаружено скопление керамики, получившее условный номер 1. Среди обнаруженных в 1967 г. находок преобладает лепная керамика. Из гончарных изделий выявлена археологически целая форма амфоры типа Харакс и амфориск Самосского производства. Этих материалов было явно недостаточно для датирования памятника. В связи с этим с целью уточнения датировки и установления характера памятника в 1999 г. были предприняты разведочные раскопки поселения в районе шурфа 1967 г. В 1999 г. первоначально был заложен раскоп размерами 10 х 4 м. В западной части раскопа были зафиксированы границы шурфа 1967 г. This article is the first publication in the form of summary the materials of excavations of settlement on the southwest slope of mountain Sokol (Kush-Kaya) near Sudak. Excavations of settlement were conducted in 1967 and in 1999. Settlement is located on south-west slope of Sokol. Archaeological material was saved only under the ledges of relief and was in the burnt gummous layers. Found out 4 accumulations of ceramics among which the fragments of clay were met with tracks of framework-pole construction. Judging to on character of location of ceramic material, buildings of settlement were obviously executed from a tree and clayed. Basic archaeological material is dated within the limits of the first half of IV - middle of VI cc. The most exact dating is given by the find of Samos amforisk, which has clear analogies of the second half of V – first half of VI cc. The amphorae of type Kharaks become obsolete in the first half of VI c. Thus, the most credible date of stopping of existence of settlement is a middle – second half of V c. That time is date stopping of life on a settlement in middle part of Taraktash backbone.